Impact of Mucuna bracteata Addition in Biofertilizer with Various NPK Doses on Sweet Corn (Zea mays saccharata Sturt.) Growth and Production - Hapsoh Hapsoh; Wawan Wawan; Dini Isna Rahma; Rifai Ahmad; Saragih Verics Abednego (E3S Web of Conferences, 2024)
The effectiveness of bacteria in biofertilizers when applied to soil is essential to ensure optimal nutrient availability for plants. This research aims to determine the best combination of oil palm compost sludge and biofertilizer enriched with M. bracteata to enhance the growth and yield of sweet corn plants while reducing the use of inorganic NPK fertilizers that negatively impact the environment. The study was conducted using a non-factorial completely randomized design (CRD) with 8 treatments and 3 replications, resulting in 24 experimental units. Each unit included different concentrations of M. bracteata (0%, 5%, 7.5%, and 10%) combined with various NPK doses (100%, 75%, and 50%). The results indicated that biofertilizer combined with 10% M. bracteata significantly increased plant height, cob weight without husks, and cob length without husks in sweet corn and reduced NPK fertilizer usage by 50%. The novelty of this research lies in its potential for eco-friendly farming practices, offering dual benefits of enhanced crop yields and reduced environmental impact.